2006
DOI: 10.1021/es0607483
|View full text |Cite
|
Sign up to set email alerts
|

The Interference of Pharmaceuticals with Endogenous and Xenobiotic Metabolizing Enzymes in Carp Liver:  An In-Vitro Study

Abstract: The interactions of fibrate (clofibrate, fenofibrate, bezafibrate, gemfibrozil), antiinflammatory (ibuprofen, diclofenac, naproxen, ketoprofen), and anti-depressive (fluoxetine,fluvoxamine, paroxetine) drugs with CYP catalyzed pathways (CYP1A, CYP3A-, CYP2K-, and CYP2M-like) and Phase II activities (UDP-glucuronosyltransferases and sulfotransferases), involved in both xenobiotic and endogenous metabolism in fish, were investigated in-vitro by incubating carp liver subcellular fractions in the presence of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…The reduction of the E max value and the augmentation of the K D value of the effective kinetics of schisandrin B on hepatic index by fenofibrate treatment suggest that the hepatotrophic action of these two drugs may be mediated by a similar biochemical mechanism. In this regard, the hepatocellular hypertrophic effect of fibric acid analogs (including fenofibrate) was found to be related to the induction of xenobiotic-metabolizing enzymes and activation of peroxisome proliferator-activated receptors, which play important roles in the metabolic regulation of lipids (Neumeier et al 2006;Thibaut et al 2006;Ren et al 2010). While the mechanism involved in the hepatotrophic action of schisandrin B remains to be determined, it may be related to the induction of xenobiotic-and/or lipidmetabolizing enzymes by this compound.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the E max value and the augmentation of the K D value of the effective kinetics of schisandrin B on hepatic index by fenofibrate treatment suggest that the hepatotrophic action of these two drugs may be mediated by a similar biochemical mechanism. In this regard, the hepatocellular hypertrophic effect of fibric acid analogs (including fenofibrate) was found to be related to the induction of xenobiotic-metabolizing enzymes and activation of peroxisome proliferator-activated receptors, which play important roles in the metabolic regulation of lipids (Neumeier et al 2006;Thibaut et al 2006;Ren et al 2010). While the mechanism involved in the hepatotrophic action of schisandrin B remains to be determined, it may be related to the induction of xenobiotic-and/or lipidmetabolizing enzymes by this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the enzymes responsible for SSRI metabolism in fish also belong to the cytochrome P-450 superfamily, as these key metabolizing enzymes are highly conserved among vertebrates and may display a similar substrate specificity. 26 In the Japanese puffer fish (Takifugu rubripes), also known as fugu, orthologous nucleotide sequences from 17 of 18 mammalian P450 families were detected. 27 Even though McArthur et al 28 observed that teleost and mammalian P450 genes belonging to the CYP3A subfamily have undergone independent diversification in the course of gene duplication events that may have coincided with the acquisition of new functions, it can be expected that SSRIs may interact with and inhibit some P450 isoenzymes in fish.…”
Section: Physicochemical Properties and Pharmacokinetics Of Ssrismentioning
confidence: 99%
“…In vitro exposures to chemicals can be regarded as surrogates of potential in vivo effects as they are likely to reveal an involvement of the enzymatic pathway in the chemical's metabolism (Thibaut et al 2006). Thus, important phase I reactions involved in xenobiotic metabolism-EROD, BFCOD and CbE activities-were screened for the potential interaction of PPCPs of environmental concern that can be found in the river basin (Fabrega et al 2013;Osorio et al 2016).…”
Section: Introductionmentioning
confidence: 99%